2017
DOI: 10.1038/s41398-017-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Clustered repetitive transcranial magnetic stimulation for the prevention of depressive relapse/recurrence: a randomized controlled trial

Abstract: Repetitive transcranial magnetic stimulation (rTMS) may have the potential to prevent depressive relapse. This assessor-blinded, randomized controlled study was designed to evaluate the efficacy and safety of rTMS as a mono- and combination therapy in the prevention of depressive relapse/recurrence. A total of 281 depressed patients who had achieved stable full or partial remission on a 6-month antidepressant (ADP) run-in treatment were randomly assigned to an rTMS (n = 91), ADP (n = 108), or combined (rTMS + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
(53 reference statements)
0
26
0
Order By: Relevance
“…This conclusion was reached in a study conducted with sixty young depressive patients who started treatment from the beginning with citalopram and sham or rTMS therapy during two weeks [169]; or a recent study with 281 depressed patients who had achieved stable full or partial remission on a 6-month antidepressant (ADP) run-in treatment and were randomly assigned to an rTMS (n=91), ADP (n=108), or combined (rTMS + ADP, n=82) treatment group for 12 months in 5-10 sessions over a 3-5-day period/monthly. This study concluded that TMS, whether as a mono-or additional therapy, is superior to antidepressants in preventing depressive relapse/ recurrence, particularly in first-episode depressed patients [170].…”
Section: Reviewmentioning
confidence: 79%
“…This conclusion was reached in a study conducted with sixty young depressive patients who started treatment from the beginning with citalopram and sham or rTMS therapy during two weeks [169]; or a recent study with 281 depressed patients who had achieved stable full or partial remission on a 6-month antidepressant (ADP) run-in treatment and were randomly assigned to an rTMS (n=91), ADP (n=108), or combined (rTMS + ADP, n=82) treatment group for 12 months in 5-10 sessions over a 3-5-day period/monthly. This study concluded that TMS, whether as a mono-or additional therapy, is superior to antidepressants in preventing depressive relapse/ recurrence, particularly in first-episode depressed patients [170].…”
Section: Reviewmentioning
confidence: 79%
“…Both rTMS alone and in combination with an antidepressant produced significantly lower relapse than the antidepressant alone (15.9% and 24.2% vs. 44.4%; P < 0.001). The authors concluded that rTMS was superior to antidepressants in preventing relapse in first‐episode depressed patients without increasing the risk of a manic switch …”
Section: Cost‐effectiveness In Rtms For Mddmentioning
confidence: 99%
“…The authors concluded that rTMS was superior to antidepressants in preventing relapse in first-episode depressed patients without increasing the risk of a manic switch. 62 In addition to accelerating the response to antidepressants in first-episode depression, rTMS may be ideal for some populations of patients who do not want to go on an antidepressant. Trials in patients who are antidepressant-naive are likely warranted.…”
Section: Rtms For First-episode Depressionmentioning
confidence: 99%
“…The major difficulty with interpreting this research is the marked heterogeneity between the maintenance schedules used across treatment. Clearly the most substantive randomized maintenance study conducted to date investigated the use of clustered maintenance rather than the more traditional schedules that have been adopted more widely in clinical practice. There is certainly a suggestion that protocols involving greater numbers of treatments are associated with better outcomes with the one study providing treatment in a single session once per month showing no benefits of active over sham therapy .…”
Section: Maintenance Strategies After a Successful Course Of Rtmsmentioning
confidence: 99%
“…By far, the largest published study investigated the efficacy of clustered maintenance. 9 Two hundred eighty-one patients who had achieved full or partial remission with antidepressant medication were randomized to rTMS, medication, or combination treatment. Treatment involved 10 sessions over a 5-day period monthly for the first 3 months and then 5 sessions over a 3-day period monthly thereafter.…”
Section: Is Maintenance Repetitive Transcranial Magnetic Stimulation mentioning
confidence: 99%